Dynamic behaviour of biomaterial reinforcements in composite systems - Tang, Seow Mun. (2009)
The tension-tension fatigue behavior of hydroxyapatite (HA) particulate reinforced polyetheretherketone (PEEK) composites were investigated, with particular interest in the influence of HA surface morphology, HA loading and applied cyclic stress. Fatigue testing was carried out under load-controlled mode, at a frequency of 5 Hz and a stress ratio of 0.1. The fatigue performance of PEEK was significantly affected by the incorporation of HA and applied cyclic stress. Generally, the fatigue life of the biocomposite decreases with an increase in either the HA content or the applied cyclic stress. The HA morphology also influences the fatigue life of the biocomposite, with the SDHA-PEEK composites exhibiting a shorter fatigue life than the SHA-PEEK composites.